Government litigation risk and the decline in low-income mortgage lending - W. Scott Frame; Kristopher Gerardi; Erik J. Mayer; Billy Y. Xu; Lawrence Chengzhi Zhao (Federal Reserve Bank of Atlanta, 2024)
We study the effect of Department of Justice lawsuits in the 2010s against large lenders for alleged fraud in the Federal Housing Administration (FHA) mortgage insurance program. The suits led to more than 5 billion in settlements and caused targeted banks and their peers to precipitously exit the FHA market. Difference-in-differences and triple differences tests exploiting geographic variation in exposure to exiting banks show a 20 percent reduction in FHA lending in heavily exposed areas. This reduction was not associated with improved underwriting standards or lower default rates. Large banks' FHA exit has significantly reduced low-income households' overall access to mortgage credit.
Keywords: G18; G21; G51; 330; household finance; banking; mortgage; credit access; litigation